A Protocol for the Investigation of the Intramolecular Vibrational Energy Redistribution Problem: the Isomerization of Nitrous Acid as a Case of Study - Duarte, Leonardo J.; Nunes, Claudio M.; FAUSTO, RUI; Braga, Ataualpa A. C. (Royal Society of Chemistry, 2025)
The conformational isomerization of nitrous acid (HONO) promoted by excitation of the nu OH or nu N 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 O stretching normal coordinates is the first observed case of an infrared-induced photochemical reaction. The energy captured by the excited normal modes is redistributed into a highly excited vibrational level of the tau OH torsion normal coordinate, which is the isomerization reaction coordinate. Herein, we present simple numerical methods to qualitatively investigate the coupling between the normal coordinates and the possible gateways for vibrational energy redistribution leading to the isomerization process. Our methodology involves the generation of the relevant 2D potential energy surface (PES), by spanning the reaction coordinate and one of the 3N - 7 projected normal coordinates along the intrinsic reaction coordinate (IRC). Once the PES has been obtained, the time-independent wavefunctions are calculated using the standard discrete variable representation (DVR) approach. The reaction barrier is investigated using the interacting quantum atoms (IQA) decomposition scheme, evidencing an important contribution from the exchange-correlation energy to the isomerization. Coupling between normal coordinates indicates preferential normal modes to redistribute the vibrational energy. 1D deep tunneling rates were found to be negligible.